Visible light‐responsive azo‐based smart materials: Design, performance, and applications in energy storage - Shurui Lv; Yuang Zhang; Wentao Wang; Shufen Zhang; Bingtao Tang (Smart Molecules)
Abstract Azobenzene and its derivatives are the most extensively investigated and applied molecular photoswitches, which can undergo reversible transformation between trans and cis isomers upon irradiation with light at specific wavelengths. Through structural geometry transformation, the property alterations can be integrated into smart materials to meet diverse application requirements. Most azo‐based photoswitches require UV light for activation. However, complete activation within the visible or even near‐infrared light range could offer several benefits for photoswitch applications, including improved biocompatibility, better light penetration, and enhanced solar light utilization efficiency. This review presents an overview of the development of visible‐light responsive azo‐based materials, covering molecular design strategies and their applications in energy storage. Recent efforts aimed at enhancing the performance of azo‐based energy storage materials are highlighted. According to the different strategies for improving energy storage properties, these materials are categorized as those that directly increase isomerization energy and those that introduce phase transition energy. Furthermore, we discuss the challenges and opportunities in this field with a view to inspire further exploration.